تقييم لتأثير كثافة النموذج الرقمي للأرض على دقة الإرجاع العامودي للصور الجوية - عمر الخليل; وائل ديوب (Tishreen University, 2018)
تستخدم منتجات المسح التصويري الرقمية في العديد من التطبيقات الهندسية. ومن أكثر هذه المنتجات استخداماً نذكر الصور الجوية المصححة عامودياً نظراً لسهولة التعامل معها مقارنةً بالخارطة التقليدية. هذا, ويعتبر النموذج الرقمي للأرض من أهم المدخلات اللازمة لتوليد هذا النوع من الصور حيث تلعب كثافته ومستوى التفاصيل فيه دوراً هاماً في تحديد الدقة النهائية لهذه الصور. عادةً ما يتم الحصول على النموذج الرقمي للأرض من خلال رقمنة خطوط الكونتور أو باستخدام نقاط تسوية موزعة داخل المشهد. ومع ظهور تقنية المسح الليزري الجوي, صار من الممكن الحصول على نماذج رقمية للأرض عالية الدقة وشديدة التفصيل ولكنها عالية الكلفة. نعرض في هذا البحث إمكانية استخدام تقنية جديدة في إنتاج هذا النموذج وهي النظم التي تحاكي الماسحات الليزرية. هذه النظم تستخدم الصور وهي قليلة الكلفة وذات دقة مقبولة. كما نناقش تأثير كثافة نقاط النموذج على النوعية البصرية والهندسية للصورة المرجعة النهائية. التحقق من الدقة سيتم باستخدام مجموعة من نقاط التحقق التي تم الحصول عليها من عملية تثليث جوي للصور الجوية المستخدمة. Digital photogrammetric products are used in many engineering applications, and the orthorrectified aerial photographs are widely used due to the ease of handling compared to conventional maps. The Digital Terrain Model (DTM) is one of the most important inputs needed to generate the orthophotos, where the intensity and the level of detail of this DTM play an important role in determining the final accuracy of these orthophotos. DTM is usually prepared by digitization of contour lines or by using leveling points distributed within the imaged scene. With appearance of aerial laser scanning technique, it became possible to obtain a high-resolution and highly detailed DTM, but with high cost. In this paper, we illustrate the possibility of using new system in the production of DTM. This system simulates the laser scanners. These systems are image-based, low-cost, and guarantee an acceptable precision. We discuss also the effect of the density of DTMs on the visual and the geometric quality of the final orthophoto. Verification of accuracy will be achieved by the of check points that have been obtained from aerial triangulation process of the used aerial images.